2021
DOI: 10.4081/aiua.2021.1.88
|View full text |Cite
|
Sign up to set email alerts
|

MRI/US fusion prostate biopsy in men on active surveillance: Our experience

Abstract: Aim: The upgrading or staging in men with prostate cancer (PCA) undergoing active surveillance (AS), defined as Gleason score (GS) ≥ 3+4 or more than 2 area with cancer, was investigated in our experience using the software-based fusion biopsy (FB). Methods: We selected from our database, composed of 620 biopsies, only men on AS according to criteria of John Hopkins Protocol (T1c, < 3 positive cores, GS = 3+3 = 6). Monitoring consisted of PSA measurement every 3 months, a clinical examination every 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Our results may be due to the 73 patients with prior negative biopsies or on AS. This subset had 18 patients with PI‐RADS 5 lesions, of which 10 had csPCa, which is similar to reported data 26 . Furthermore, Hambrock et al .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results may be due to the 73 patients with prior negative biopsies or on AS. This subset had 18 patients with PI‐RADS 5 lesions, of which 10 had csPCa, which is similar to reported data 26 . Furthermore, Hambrock et al .…”
Section: Discussionsupporting
confidence: 86%
“…This subset had 18 patients with PI-RADS 5 lesions, of which 10 had csPCa, which is similar to reported data. 26 Furthermore, Hambrock et al also demonstrated 31 of 46 tumours were anterior in a series of men with repeated negative biopsies, 27 suggesting that anterior lesions may account for missed diagnosis in men with previous biopsies. If we only assessed biopsy-naïve men with PI-RADS 5 lesions, 85% (6 out of 7) demonstrate csPCa which is in line with expectations.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, an adequate number of needle cores allows to select patients with high volume GG1 PCa at risk of reclassification during follow up (33.4% of the cases) (30). In this respect, the number of systematic and/or targeted biopsy cores is an independent predictor for selection of patients with unfavourable characteristics for AS (31)(32)(33)(34)(35). On the other hand, a relevant critical point remain the adherence of patients to scheduled AS follow up; in fact, the estimated drop out to the execution of repeated prostate biopsy at 1 vs. 4 vs. 7 years from initial diagnosis is equal to 11 vs. 30 vs. 29%, respectively (3); therefore, the European Association of Urology (EAU) guidelines strongly recommend to perform repeat biopsy in the presence of clinical suspicion of PCa progression (i,e., PSAD evaluation, progression on mpMRI) instead to repeat biopsies at scheduled times that, anyway, are suggested every three years (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…4,20 Lacetera et al found that using an MRI/US fusion biopsy technique more than doubled the detection of clinically significant disease in men on AS. 21 We defined a post-operative Gleason grade of ≥7 as being clinically significant as this would have resulted in patients being classified as having a higher risk disease pre-operatively using both the CPG and EAU models. AS is a well-established management option in the context of CPG 1 and EAU low-risk disease.…”
Section: Lower Confidence Intervalmentioning
confidence: 99%